Bacterial Otitis by Klebsiella sp. as a Cause of Encephalitis in a Cat - da Silveira, Elissandra; Vidor, Silvana Bellini; Dhein, Juliana de Oliveira; Gonzalez, Paula Cristina Sieczkowski; Spanamberg, Andréia; Sonne, Luciana; Amorim da Costa, Fernanda Vieira (Acta Scientiae Veterinariae, 2018)
Background: Meningoencephalitis in cats is usually related to infectious diseases but may also be caused by the extension of bacterial infections originated in the middle or inner ear. This paper seeks to report on a case of encephalitis due to an infection in the middle/inner ear in a 15-year-old cat. The diagnosis was made through brain CT scan and culture and antibiogram of material collected during a ventral osteotomy of the tympanic bulla and reported grave intravascular haemolysis associated to the treatment with antimicrobial imipenem with cilastatin sodium that has already been described in humans but not in small animals in the researched literature. Case: A 15-year-old, male, castrated, Siamese cat was brought to the Veterinary Clinical Hospital of the UFRGS. The animal presented pyrexia and hyporexia, tested negative in the immunoenzymatic test to detect antigens of the FeLV and antibodies of the FIV. The animal had a history of three episodes of tonic convulsion within two days and otitis that had gone untreated for 10 months prior to the consultation, with apparent spontaneous remission. After blood tests, serum biochemistry profile, abdominal ultrasound scan, chest x-rays and CT scan was requested. It revealed middle and inner otitis in the right ear. It was performed a ventral osteotomy of the right tympanic bulla. Material was collected for culture and antibiogram. It was confirmed that the animal had an inner otitis of bacterial origin by multi-resistant Klebsiella spp. that was sensitive only to antimicrobial imipenem with cilastatin sodium. Fifteen days into the treatment with this antibacterial combination, grave haemolysis was observed, probably associated to the use of the medicine. The patient died on the 17th day of the treatment which was not interrupted as per its owner’s decision. At necropsy, both in the tympanic bulla and liver were found mucous content and whitish lumps. The material collected from the tympanic bulla and cerebrospinal liquid were cultured post-mortem when the bacteria Klebsiella sp. was isolated in the CNS and no bacterial growth was observed in the right tympanic bulla. Discussion: This makes it possible to deduce that there was an intracranial expansion of the otitis which would explain the convulsions and, that due to the use of the antimicrobial agent, the growth of Klebsiella sp. in the tympanic bulla was inhibited. The final diagnosis was bacterial otitis with probable bacterial migration to the brain and liver. Suppurative meningoencephalitis caused by the expansion of the inflammation deriving from middle/inner otitis has been reported as being the cause of convulsions in cats with bacterial isolation. The bacteria that was isolated from the tympanic bulla is in agreement with the microbiota present in middle/inner otitis in cats. Regarding haemolysis, there are no reports that link the use of carbapenems in small animals to it or that mention what the safe therapeutic dosage should be if they were administered. Regarding humans, there have been various reports of haemolytic anaemia caused by this type of medicine including carbapenems. It is also known that, in in vitro tests, imipenem may cause inhibition due to competition from human erythrocyte-glutathione reductase, in charge of defending the erythrocyte against haemolysis. It has been concluded that meningoencephalitis caused by middle/inner otitis must be included as a differential diagnosis in case of convulsions in cats. Additionally, further studies must be carried out in order to determine both the efficacy and the toxicity of carbapenems in veterinary patients, including studies of the occurrence of grave haemolysis after they are administered. Keywords: meningoencephalitis, computed tomography, convulsions, imipinem, carbapenems.